2011
DOI: 10.1007/s11046-011-9418-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole-, Amphotericin-B-, Caspofungin-, and Anidulafungin-Resistant Candida ciferrii: An Unknown Cause of Systemic Mycosis in a Child

Abstract: Candida ciferrii, which is known as an agent of superficial yeast infection and onychomycosis, has rarely been isolated as an agent of candidemia. Limited reports have suggested different patterns of antifungal sensitivity. We report a rare candidemia case caused by c.ciferrii in an 8-year-old child in which isolated candida species were resistant to amphotericin-B (MIC > 1 μg/ml), fluconazole, (MIC ≥ 64 μg/ml), caspofungin (MIC ≥ 32 μg/ml), and anidulafungin (MIC ≥ 32 μg/ml) but sensitive to voriconazole (MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
17
1
1
Order By: Relevance
“…[10], but it is still very important to identify and to test antifungal susceptibilities in relevant clinical isolates as exemplify in this case, in which the susceptibility of the strain to fluconazole was MIC = 32 μg/ml and the patient did not respond clinically, while others reports of this species have shown different susceptibilities [6]. Finally, it was necessary to use posaconazole, a broadspectrum drug, to treat this patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10], but it is still very important to identify and to test antifungal susceptibilities in relevant clinical isolates as exemplify in this case, in which the susceptibility of the strain to fluconazole was MIC = 32 μg/ml and the patient did not respond clinically, while others reports of this species have shown different susceptibilities [6]. Finally, it was necessary to use posaconazole, a broadspectrum drug, to treat this patient.…”
Section: Discussionmentioning
confidence: 99%
“…ciferrii is an infrequent pathogen, which has been reported on several occasions as a causative agent of human infection and almost always in risk populations [6,8,9]. In the literature it has not been reported that an isolation of this agent from blood in an adult and neither associated to a CVC, but Agin et al reported a fatal case of a child in which they isolated a multi-resistant strain of C. ciferri from a blood culture [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have reported C. ciferrii (teleom. Stephanoascus ciferrii) to cause invasive fungal infections in humans (Gunsilius et al, 2001;Agin et al, 2011). The remaining 4.1% of the detected yeast sequences affiliated with an uncultured clone related with the genus Pichia, detected in agarwood.…”
Section: Phylogenetic Analyses Of Fungimentioning
confidence: 99%
“…For the uncommon Candida species we refer the reader to the general recommendations regarding diagnosis and treatment as described in the ESCMID Candida guideline [1][2][3][4][5][6]. However, as some of these species are characterized by unique intrinsic susceptibility patterns, which are not specifically addressed in the Candida guidelines, a table summarizing this information has been elaborated and included here ( Table 1, [7][8][9][10][11][12][13][14][15][16][17][18][19]). This table also includes names used in the anamorphic and teleomorphic states, despite this distinction recently being made superfluous [20].…”
Section: Introductionmentioning
confidence: 99%